Economic Policy from the Perspective of Contemporary Challenges in Economic History – Hopes, Concerns and Dilemmas - Słodowa-Hełpa, Małgorzata (Studia Historiae Oeconomicae, 2020)
The article, written on the basis of a critical review of the latest Polish and foreign-language literature, materials from websites and the author’s experience gained from previous research, is treated as a voice in the discussion on new challenges and the need for historical research on economic policy in its various dimensions and contexts, and on the possibilities in this field. The premises which determined the title, nature and scope of the study were highlighted in the introduction. The following three parts attempt to answer the following questions in sub-headings: why is the turn to the problems of economic policy particularly desirable now? What premises justify and enable intensification of historical research on economic policy problems? How to study the past of economic policy to participate in managing the present and creating the future?